A Study of Ronald Dworkin’s Thought on Legal Positivism - Ujung, Pendi; Maria Ulfa; , Hendra Sudarsin; Usman, Sopar; Parningotan Malau (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2025)
This paper provides an overview of Dworkin's view of legal positivism, particularly his understanding of law as more than a set of rules as Dworkin explains Defending Dworkin explains Dworkin's critique of legal positivism as concerning the principal claim of positivism which stipulates that the existence of law is determined exclusively by its formal source, methodology, or process and therefore, irrelevant is anything moral. Dworkin explains law as integrity, that legal reasoning or legal argumentation is required to be the best moral reasoning to make sense of the legal system. This paper adopts normative-philosophical research methods, using comparative and analytical methods to study legal positivism (Austin and Kelsen) alongside Dworkin's interpretive methodology. The study shows that Dworkin's philosophy of law integrates moral thinking and the theory of justice within the legal process and justice and legal reasoning. Dworkin's critique of legal philosophy, particularly reductivism and legal positivism, advocates a legal philosophy that is closer to the ideals of morality.